2004
DOI: 10.1111/j.1365-2982.2004.00539.x
|View full text |Cite
|
Sign up to set email alerts
|

High‐resolution manometry predicts the success of oesophageal bolus transport and identifies clinically important abnormalities not detected by conventional manometry

Abstract: The HRM predicts bolus movement more accurately than conventional manometry and identifies clinically relevant oesophageal dysfunction not detected by other investigations including conventional manometry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
213
0
4

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 223 publications
(223 citation statements)
references
References 30 publications
6
213
0
4
Order By: Relevance
“…High resolution manometry allows a more detailed evaluation of the relaxation of the upper and lower esophageal sphincter and esophageal peristalsis. Recent studies indicate that it might be superior to conventional manometry in predicting bolus transit 3,4 .…”
Section: Introductionmentioning
confidence: 99%
“…High resolution manometry allows a more detailed evaluation of the relaxation of the upper and lower esophageal sphincter and esophageal peristalsis. Recent studies indicate that it might be superior to conventional manometry in predicting bolus transit 3,4 .…”
Section: Introductionmentioning
confidence: 99%
“…Such patients who are thought to have variants of achalasia respond well to LOS-disruptive procedures (Hirano et al, 2001). HRM in patients who have usually little if any oesophageal dilatation and varying abnormalities of oesophageal body function has shown that the orad excursion of the LOS during swallowing is preserved (Clouse et al, 2000;Hirano et al, 2001;Staiano et al, 2001;Fox et al, 2004), explaining why "conventional" assessment of swallow-induced LOS relaxation with a single stationed side hole or transducer fails to detect the impaired relaxation (Fig. 4).…”
Section: Understanding Abnormal Resistance To Flow Into the Stomach Fmentioning
confidence: 99%
“…The spatial resolution of HRM is sufficient to allow monitoring of the pressure profile across even small hiatus hernias (Fox et al, 2004) (Fig. 3).…”
Section: Dissection Of the Mysteries Of Hiatus Herniamentioning
confidence: 99%
See 1 more Smart Citation
“…This might be due to widely spaced sensors in the catheter. Due to large number of sensors, HRM is expected to have higher fidelity to diagnose esophageal motility disorders, which has been documented in the literature [9]. One of the many advantages of the Clouse plot in HRM is the ease with which different esophageal motility disorders can be grossly recognized by the experienced motility doctors, but in the era of super-speciality health care using evidenced-based medicine and various mathematical scoring systems, are the doctors and patients happy with gross recognition of disorders?…”
mentioning
confidence: 99%